Imaging characteristics and treatment of a penetrating brain injury caused by an oropharyngeal foreign body in a dog. Issue 3 (20th July 2017) - McKenzie, Jennifer; Cooper Murphy, Megan; Broome, Cameron; Tayari, Hamaseh; Gutierrez‐Quintana, Rodrigo
Abstract: A 4‐year‐old Border collie was presented with one episode of collapse, altered mentation, and a suspected pharyngeal stick injury. Magnetic resonance imaging (MRI) and computed tomography showed a linear foreign body penetrating the right oropharynx, through the foramen ovale and the brain parenchyma. The foreign body was surgically removed and medical treatment initiated. Complete resolution of clinical signs was noted at recheck 8 weeks later. Repeat MRI showed chronic secondary changes in the brain parenchyma. To the authors' knowledge, this is the first report of the advanced imaging findings and successful treatment of a penetrating oropharyngeal intracranial foreign body in a dog.